Peace, Pastors, and Politics: Tactics of Resistance in East Germany - Silva, Brendan R. Ozawa-De (A journal of church and state, 2005)
Brendan R. Ozawa-De Silva; Peace, Pastors, and Politics: Tactics of Resistance in East Germany, Journal of Church and State, Volume 47, Issue 3, 1 July 2005, Pa